Effectiveness, spillovers, and well-being effects of driving restriction policies - Luis Sarmiento; Nicole Wägner; Aleksandar Zaklan (Deutsches Institut für Wirtschaftsforschung (DIW), 2021)
We study the effectiveness, spillovers, and well-being effects of low emission zones in Germany, an emission-intensity-based driving restriction rapidly growing in popularity. Using regression discontinuity and group-time difference-in-differences designs, we show that previous estimates of the policy's impact on traffic-related air pollution significantly underestimate its effectiveness. We provide evidence of beneficial and harmful policy spillovers to neighboring areas, and increases in ozone due to changes in the chemical balance with precursor contaminants. Policy effects are heterogeneous by season, with greater decreases in traffic pollutants during winter and increases in ozone during spring and summer. Using individual-level data from the German Socio-Economic Panel, we further find that the policy decreases subjective well-being despite clear evidence of health benefits. The decline in well-being is especially pronounced in the first year after policy implementation and is transitory.
Keywords: Q53; Q58; I31; I18; 330; low emission zones; air pollution; well-being; health; group-time differencein-differences; regression discontinuity